PENGEMBANGAN MODUL ELEKTRONIK BERBASIS LECTORA INSPIRE PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK - Hervina Kiruna; Massus Subekti; Purwanto Gendroyono (Fakultas Teknik Universitas Negeri Jakarta, 2018)
The aims of this study are to : (1) find the necessity of electronic module, (2) find the process of the development module, (3) find the expediency, and (4) find the effectiveness of the electronic module based on Lectora Inspire on the subject Electric Motor Installation. The research method used is Research and Development method, while the product development model uses the ADDIE (Analysis,Design, Development, Implementation, and Evaluation). This study uses questionnaire and questions test as the technique of collection data. The results of the study find that : (1) the analysis of the necessity of electronic module shows that as many 100% of the students have not used the electronic module yet, (2) the process of developing the learning as module is done in fivemain stages, which are Analysis,Design, Development, Implementation, and Evaluation, (3) feasibility testing is obtained on average 3,5 with the criteria “Very feasible” and concludes that the electronic module based on Lectora Inspire on teh subject Electric Motor Installation is feasible for learning., and (4) the effectiveness test is done by comparing the posttest grade of the experimental class with the posttest grade of the control class has the result of Tcount = 5,74 with the conlusion that the effectiveness of the use of Electronic Module based Lectora Inspire is higher or equal to the students that do not use the module in improving the learning outcomes of Electronic Motor Installation. Abstrak Penelitian ini bertujuan untuk: (1) mengetahui kebutuhan modul elektronik (2) mengetahui proses pengembangan modul, (3) mengetahui kelayakan dan (4) mengetahui keefektifan modul elektronik berbasis Lectora Inspire pada mata pelajaran Instalasi Motor Listrik. Metode penelitian yang digunakan adalah metode penelitian dan pengembangan (Research & Development) sedangkan model pengembangan produk yang digunakan adalah model ADDIE (Analysis,Design,Development,Implementation, dan Evaluation). Teknik pengumpulan data pada penelitian ini menggunakan angket dan soal tes. Hasil penelitian menunjukan bahwa: (1) analisis kebutuhan mengatakan sebanyak 100% siswa belum menggunakan modul elektronik (2) proses pengembangan modul pembelajaran dilakukan dalam lima tahapan utama yaitu Analysis,Design,Development,Implementation, dan Evaluation; (3) pengujian kelayakan didapatkan rata-rata 3,5 dengan kriteria “sangat layak” dan modul elektronik berbasis Lectora Inspire pada mata pelajaran Instalasi Motor Listrik layak digunakan untuk proses pembelajaran; dan (4) pengujian keefektifan dilakukan dengan membandingkan nilai posttest kelas eksperimen dengan nilai posttest kelas kontrol didapatkan hasil nilai